ISOLATIO AD CHARACTERIZATIO OF EDOPHYTIC BACTERIA FROM ROOTS OF POGAMIA GLABRA VET . - RUBY E JALGAONWALA; RAGHUNATH T MAHAJAN (International Journal of Pharma and Bio Sciences, 2011)
Endophytic bacteria have been isolated from roots of pongamia glabra.,belonging to Jalgaon Maharashtra (India) during different environmental conditions. A total of sixteen endophytic bacteria were isolated from the underground parts using suitable triple surface sterilization protocol. Bacterial isolates were screened with the aim to produce antifungal metabolites for their possible activities using dual culture method. Bacterial isolate possessing great antifungal activity was identified and characterized according to Bergeys manual of systematic bacteriology as Bacillus megaterium.